PENGARUH PENGETAHUAN DAN MOTIVASI TERHADAP MINAT BERINVESTASI DI PASAR MODAL PADA UNIVERSITAS TRIATMA MULYA - Guido Samuel Agung Wijaya; Saortua Marbun (Journal Research of Management, 2021)
This study aims to analyze and prove the influence of knowledge and motivation on interest in investing in the capital market. This research uses a descriptive method with a quantitative approach. The sampling technique used is simple random sampling, which is a random sampling technique for members of the population to be sampled. The number of respondents used the Slovin formula so that the sample used was 56 students of Triatma Mulya University. Multiple linear regression analysis using SPSS software version 24. Regression equation obtained: 4.215 + 0.564X1 + 0.331X2. The results showed that: first knowledge about investment has a positive and significant effect on interest in investing in the capital market, second motivation has a positive effect on students' interest to invest in the capital market and lastly knowledge and motivation together positively affect investment interest on the capital market. This adequate knowledge will shape a person's ability to gain profits and also be able to manage risks that exist both small and large so as to reduce the impact of losses that will be experienced. This risk factor is considered by potential investors to be able to invest in the capital market.